The effect of Affordable Care Act on the competition in the post-patent ethical drug market. Issue 3 (26th August 2014) - Vivek Pande, Dr.; Yu, Yu; Zhao, Yi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to study the post-patent ethical drug market and simulate the impact of Patient Protection and Affordable Care Act (ACA) on individuals, health-care providers and pharmaceutical firms. US policymakers have been looking at various ways to curb rising health-care costs in USA, including ways to promote the use of generic drugs in lieu of brand drugs. In this broader context, the implementation of ACA in December 2013 will introduce major changes in the pharmaceutical market. Design/methodology/approach – To fully understand the impact of such policy changes, we develop a structural model to study consumers' buying behavior and firm competition in the post-patent ethical drug markets. We use the estimated model parameters to conduct four policy simulations to illustrate the effect of Obamacare on increasing the relative size of price-insensitive segment, reducing price sensitivity in the price-sensitive segment, providing brand price discount to Medicare patients previously in the "donut hole" and the effect of change in people's attitude toward generics. Findings – Our model estimation reveals two classes of consumers with different price sensitivities. This heterogeneity explains the increase in the brand price after generic entry. We identify consumers' switching costs between generic and brand drugs, as well as among different generics. From the policy simulation, we find that except the closure of Medicare donut hole, all other policy changes lead to increased usage of the focal molecule, and the efforts to increase insurance coverage and reduce the out of pocket payment for prescription drugs lead to increase in firm profit. Originality/value – This paper is the first to illustrate the potential policy effect of Obamacare through a structural model on post-patent ethical drug market.